Pengaruh Tax Planning, Tax Avoidance dan Leverage Terhadap Firm Value - Daniel Artha Wahyuda; Mira Falatifah; Lady Karlinah (Owner : Riset dan Jurnal Akuntansi, 2025)
This study analyzes the effects of tax planning, tax avoidance, and leverage on firm value in Consumer Cyclicals and Non-Cyclicals companies listed on the Indonesia Stock Exchange during the period 2020–2022. The research design used in this study is a quantitative method. Data were sourced from financial statements through www.idx.co.id. The techniques of data analysis are descriptive statistics, classical assumption tests, and multiple linear regression using the Random Effect Model (REM). Hypothesis testing was conducted by using a t-test for partial effects and F-tests for simultaneous effects. The results show that, on a partial basis, tax planning and tax avoidance do not have any significant impact on firm value, while on the other hand, leverage has a positive and significant effect on firm value. Aggregately, the three independent variables comprising tax planning, tax avoidance, and leverage substantially affect firm value. The findings of this research suggest that leverage is a critical factor in enhancing a firm's value, while tax strategies, although effective in reducing tax obligations, may not be considered as a key determinant in the valuation of investors. In this regard, the findings suggest that management should exercise caution when engaging in aggressive tax strategies, because most investors are more concerned about long-term stability and good corporate governance. Keywords: Tax Avoidance; Tax Planning; Leverage; Firm Value